1996
DOI: 10.1084/jem.184.4.1233
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of the lipooligosaccharide synthesis locus lgt among strains of Neisseria gonorrhoeae: requirement for lgtE in synthesis of the 2C7 epitope and of the beta chain of strain 15253.

Abstract: SummaryThe present study was undertaken to examine the extent to which the ~t locus varies among strains of gonococci. This locus encodes five glycosyl transferases involved in the synthesis of the lipooligosaccharide (LOS) of Neisseria gonorrhoeae. We examined seven gonococcal strains and found that the structure of the lgt locus is conserved among six of these strains. The locus is strikingly altered in strain 15253. This is one of the few strains where extensive structural analysis of its LOS is available, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 39 publications
0
39
0
Order By: Relevance
“…M13761) (42); hence, the pNGLGTF::erm construct was nonpolar, as it was devoid of the transcriptional terminator. Furthermore, the presence of glucosamine (GlcNAc is added by rfaK to make the ␥-chain) was determined by carbohydrate analysis of MS11 lgtF LOS by high-pH anion-exchange chromatography (2,16), confirming the nonpolar nature of the mutation (data not shown).…”
Section: Reagentsmentioning
confidence: 89%
“…M13761) (42); hence, the pNGLGTF::erm construct was nonpolar, as it was devoid of the transcriptional terminator. Furthermore, the presence of glucosamine (GlcNAc is added by rfaK to make the ␥-chain) was determined by carbohydrate analysis of MS11 lgtF LOS by high-pH anion-exchange chromatography (2,16), confirming the nonpolar nature of the mutation (data not shown).…”
Section: Reagentsmentioning
confidence: 89%
“…Anti-LPS antibodies were measured as follows: a suspension of LPS (purified from strain KW20 by hot phenol-water extraction as described [4]) was diluted to 10 g per ml in Dulbecco's phosphate-buffered saline (PBS; Hyclone, Logan, Utah) containing 10 mM MgCl 2 and was used to coat Immulon 2HB plates (Dynex Technologies, Inc., Chantilly, Va.) (100 l per well). Plates were incubated overnight at 4°C and then wells were filled with blocking solution consisting of 5% bovine serum albumin fraction V (Sigma) in PBS containing 0.2% Tween 20, and the plates were incubated for 1 h. The wells were washed once with PBS-0.2% Tween 20 using an automatic plate washer (model 96PW; TECAN U.S., Hillsborough, N.C.).…”
Section: Methodsmentioning
confidence: 99%
“…The biochemical functions of LgtABCD have been demonstrated and correspond to the functions inferred from analysis of mutations in these genes (3,30,31). While there is significant genetic evidence supporting the function of LgtE as the glycosyltransferase responsible for the addition of galactose ␤-1,4 to glucose (6,11,14,26), biochemical data supporting this assignment have been lacking. Furthermore, since the addition of galactose ␤-1,4 to glucose can occur on both the ␣ and ␤ chains, it is unclear if LgtE is responsible for both of these biosynthetic processes.…”
Section: Discussionmentioning
confidence: 99%
“…However, purified LgtE was unable to mediate the transfer of galactose to synthetic LOS biosynthesis intermediates (30). Erwin et al (6) showed that when lgtE was nonfunctional, galactose was not added to the ␤ chain. However, no direct biochemical evidence was presented to implicate LgtE directly in this addition.…”
mentioning
confidence: 99%
See 1 more Smart Citation